Out of the mountains: the coming age of the urban guerrilla - Kilcullen, David (Oxford Univ. Press, 2013)
"In Out of the Mountains, David Kilcullen, one of the world's leading experts on modern warfare, offers a groundbreaking look ahead at what may happen after the war in Afghanistan ends. It is a book about future conflicts and future cities, about the challenges and opportunities that four powerful megatrends are creating across the planet. And it is about what national governments, cities, communities and businesses can do to prepare for a future in which all aspects of human society-including, but not limited to, conflict, crime and violence-are rapidly changing. Kilcullen analyzes four megatrends--population growth, urbanization, coastal life, and connectedness-and concludes that future conflict is increasingly likely to occur in sprawling coastal cities, in underdeveloped regions of the Middle East, Africa, Latin America and Asia, and in highly networked, connected settings. He ranges across the globe, from Kingston to Mogadishu to Honduras to Benghazi to Mumbai. Mumbai exemplifies the trend: a coastal megacity, terrorists based in nearby Karachi exploited new forms of connectivity to direct a horrific terrorist attack. Kilcullen also offers a unified theory of "competitive control" that shows how non-state armed groups, drug cartels, street gangs, warlords--draw their strength from local populations, providing useful ideas for dealing with these groups and with diffuse social conflicts in general. But for many of the struggles we will face, he notes, there will be no military solution. We will need to involve local people deeply to address problems which neither outsiders nor locals alone can solve. These collaborations will interweave the insight only locals can bring, with outsider knowledge from fields such as urban planning, systems engineering, alternative energy technology, conflict resolution and mediation, and other disciplines. Deeply researched and compellingly argued, Out of the Mountains provides an invaluable roadmap to a future that will increasingly be crowded, urban, coastal, connected-and dangerous"--